Fatores predisponentes para amputação de membro inferior em pacientes diabéticos internados com pés ulcerados no estado de Sergipe - Nunes, Marco Antonio Prado (2006)
OBJECTIVE: To determine the predisposing factors for amputation of lower limbs in diabetic patients with foot ulceration. METHODS: The research was carried out in hospitals, and all diabetic patients with foot ulceration were included. Amputation was studied in relation to age, sex, previous amputation, number of ulcers, time of diagnosis of diabetes mellitus, time of ulceration, average number of days in hospital, Wagner's classification, and presence of foot pulse. RESULTS: We verified that 55% (44/80) of the patients progressed to some type of amputation of the lower limbs; mean age was 61 years, but the occurrence of amputation was significantly higher in the age group between 60 and 90 years (P = 0.03). We did not observe a significant variation in the following variables: time of diagnosis of diabetes, time of ulceration, and hospitalization time in relation to the group of patients who were amputated. Nevertheless, the most severe lesions, when evaluated by Wagner's classification (P <0.001) and by the absence of both distal pulses (P <0.001) of lower limbs, turned out to be very significant in relation to the amputation outcome. CONCLUSION: The severity of lesions, the absence of pulse and age over 60 years were considered predisposing factors for amputation in these patients.